Reconstructing Local Wisdom Based Character Education for Sekaa Teruna Teruni in Desa Pakraman Ubud Bali - Sanjaya, Dewa Bagus (International Research Journal of Management, IT & Social Sciences, 2017)
Character plays a role as a steer and power to keep the nation from imbalance. The character does not come by itself but has to be built and formed to become a nation with dignity (Winataputra, 2012). The aim of this study was to construct local wisdom-based character education for Sekaa teruna-teruni in Desa Pakraman Ubud, Bali. This study used qualitative design to describe and to give an actual, factual, natural, holistic, and emic account about the local wisdom-based character education in Desa Pakraman Ubud, Bali.The subjects consisted of (1) government officials of theÂ  desa dinas, (2) Prajuru desa pakraman, (3) the community of the desa pakraman Ubud, (4) Sekaa teruna-teruni (youth organization), determined purposively...